A case of Legionnaires' disease with severe rhabdomyolysis misdiagnosed as COVID-19. Issue 12 (December 2022) - Sayinalp-Arslan, Basak; Er, Ahmet Gorkem; Yildirim, Mehmet; Kilicaslan, Banu; Akinci, Seda Banu; Uzun, Omrum
Abstract: Background: COVID-19 case numbers have begun to rise with the recently reported Omicron variant. In the last two years, COVID-19 is the first diagnosis that comes to mind when a patient is admitted with respiratory symptoms and pulmonary ground-glass opacities. However, other causes should be kept in mind as well. Here we present a case of Legionnaires' disease misdiagnosed as COVID-19. Case presentation: A 48-year-old male was admitted with complaints of dry cough and dyspnea. Chest computed-tomography revealed bilateral ground-glass opacities; therefore, a preliminary diagnosis of COVID-19 was made. However, two consecutive COVID PCR tests were negative and the patient deteriorated rapidly. As severe rhabdomyolysis and acute renal failure were present, Legionnaires' disease was suspected. Urine antigen test for Legionella and Legionella pneumophila PCR turned out to be positive. The patient responded dramatically to intravenous levofloxacin and was discharged successfully. Discussion: Legionnaires' disease and COVID-19 may present with similar signs and symptoms. They also share common risk factors and radiological findings. Conclusions: Shared clinical and radiological features between COVID-19 and other causes of acute respiratory failure pose a challenge in diagnosis. Other causes such as Legionnaires' disease must be kept in mind and appropriate diagnostic tests should be performed accordingly. Abstract : SARS-CoV-2; COVID-19 pandemic; legionella; rhabdomyolysis.